Mitochondrial antioxidant elamipretide improves learning and memory impairment induced by chronic sleep deprivation in mice - Yue‐Ming Zhang; Ya‐Tao Wang; Ru‐Meng Wei; Xue‐Yan Li; Bao‐Ling Luo; Jing‐Ya Zhang; Kai‐Xuan Zhang; Shi‐Kun Fang; Xue‐Chun Liu; Gui‐Hai Chen (Brain and Behavior, 2024)
Abstract Background The inflammation and synaptic dysfunction induced by mitochondrial dysfunction play essential roles in the learning and memory impairment associated with sleep dysfunction. Elamipretide (SS‐31), a novel mitochondrion‐targeted antioxidant, was proven to improve mitochondrial dysfunction, the inflammatory response, synaptic dysfunction, and cognitive impairment in models of cerebral ischemia, sepsis, and type 2 diabetes. However, the potential for SS‐31 to improve the cognitive impairment induced by chronic sleep deprivation (CSD) and its underlying mechanisms is unknown. Methods Adult c57BL/6J mice were subjected to CSD for 21 days using an activity wheel accompanied by daily intraperitoneal injection of SS‐31 (5 mg/kg). The novel object recognition and Morris water maze test were used to evaluate hippocampus‐dependent cognitive function. Western blotting and reverse transcription‐quantitative polymerase chain reaction assays were used to determine the effects of CSD and SS‐31 on markers of mitochondria, inflammation response, and synaptic function. Enzyme‐linked immunosorbent assays were used to examine the levels of proinflammatory cytokines. Results SS‐31 could improve the cognitive impairment induced by CSD. In particular, SS‐31 treatment restored the CSD‐induced decrease in sirtuin 1 (SIRT1) and peroxisome proliferator‐activated receptor γ coactivator alpha levels and the increase in levels nuclear factor kappa‐B and inflammatory cytokines, including interleukin (IL)‐1β, IL‐6, and tumor necrosis factor‐alpha. Furthermore, SS‐31 significantly increased the levels of brain‐derived neurotrophic factor, postsynaptic density protein‐95, and synaptophysin in CSD mice. Conclusion Taken together, these results suggest that SS‐31 could improve CSD‐induced mitochondrial biogenesis dysfunction, inflammatory response, synaptic dysfunction, and cognitive impairment by increasing SIRT1 expression levels.